The Epistemics of Policymaking: from Technocracy to Critical Pragmatism in the UN Sustainable Development Goals - Kris Hartley (International Review of Public Policy)
This essay examines epistemological tensions inherent in the UN Sustainable Development Goals (SDG) project. The clash between the totalizing logic of the SDGs and growing populist antipathy for expert governance can be better understood and potentially mediated through a critical pragmatist view. For the SDGs, technocratic fundamentalism not only serves the ambition for universality but also ensures epistemic stability in problem framing and protects the interests that benefit from it. However, technocratic fundamentalism also undermines the mechanics of SDG localization, working against their stated aims of justice, transparency, and institutional equity; in this way, a global development agenda shaped by myopic epistemics does itself no favors on elements by which it proposes to be measured. Compounding these epistemic tensions, anti-expert and anti-intellectual populism is confronting the credibility of technocracy and governance more generally, with possible implications for national and local policymaking informed by the SDGs. The concept of critical pragmatism, as articulated by Forester, presents both a provocation to the SDG project and a vision for imparting a more participatory orientation to it. This essay elaborates on these points.